2000
DOI: 10.1046/j.1365-3008.2000.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians and reptiles of the Dominican Republic: species of special concern

Abstract: . dorsalis) are rare and may never listed, evidence must exist that: (1) populations are have been common. Their size and habits render them dwindling, (2) the range is shrinking, or (3) a species vulnerable to predation by the introduced mongoose and must be vulnerable to exploitation and historically rare.to decimation by humans who fear and dislike them. Two iguanas (Cyclura cornuta, C. ricordii ), two turtles (Trachemys decorata, T. stejnegeri vicina), and one crocodilian (Crocodylus acutus) have been expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The Sierra de Bahoruco National Park covers the provinces of Barahona, Independencia, and Pedernales. The Jaragua National Park in Pedernales Province is a recognized international biodiversity hotspot [9][10][11]. In addition, the Biological Reserve Loma Charco Azul is also located within the RBJBE [1].…”
Section: The Rbjbe Biosphere Reserve At Glancementioning
confidence: 99%
See 1 more Smart Citation
“…The Sierra de Bahoruco National Park covers the provinces of Barahona, Independencia, and Pedernales. The Jaragua National Park in Pedernales Province is a recognized international biodiversity hotspot [9][10][11]. In addition, the Biological Reserve Loma Charco Azul is also located within the RBJBE [1].…”
Section: The Rbjbe Biosphere Reserve At Glancementioning
confidence: 99%
“…The biodiversity of Lake Enriquillo and its surroundings (conservation zone 1) includes more than 65 native, endemic, and migratory birds, and endemic species of iguanas (Cyclura cornuta and Cyclura ricordii) and the American crocodile [8,11,13]. On May 14, 1974, Law 664 created national parks in Lake Enriquillo, Isla Cabrito, and other protected areas.…”
Section: The Rbjbe Biosphere Reserve At Glancementioning
confidence: 99%
“…The Lake contains archaeological heritage dating back to the pre-Hispanic settlements of different aboriginal cultures. Its surroundings contain important biodiversity that includes more than 65 native, endemic, and migratory birds, the endemic species of iguanas (Cyclura cornuta and Cyclura ricordii) [35,36], and the American crocodile [37]. Figure 3 shows some pictures with Cyclura cornuta around Lake Enriquillo.…”
Section: Biosphere Reserves and Protected Areas Around Boca De Cachó Nmentioning
confidence: 99%
“…It is largely because of the startling decline in the genus Alsophis over the past 100 years that Dodd (1993) observed that 'the highest priority region for snake conservation concern today is the West Indies.' This region also includes Endangered and Critically Endangered colubrid snakes of the genera Ialtris, Chironius and Liophis (IUCN, 1996;Powell et al, 2000). For example, the Barbados racer Liophis perfuscus, which is probably already extinct (Underwood et al, 1999), and the Saint Lucia racer L. ornatus, which survives as a relict population on a 10-ha island off the South coast of St Lucia (Corke, 1987).…”
Section: Relevance To Other Species Conservation Programmesmentioning
confidence: 99%